Designing a cost-effective policy mix for transition toward net-zero emissions: a case study of the mid-term plan by 2035 of Taiwan - Yi-Hua Wu; Tsung-Chen Lee (Carbon Management)
This study explores the design of a cost-effective climate policy mix for transition toward net-zero emissions in the mid-term (by 2035). Its novelty lies in the methodological advancements through the development of a soft-linking procedure that integrates a top-down computable general equilibrium model with a bottom-up energy system model. The integrated assessment focuses on the climate policy mix under the framework of Taiwan’s Climate Change Response Act passed in 2023. The analysis shows that a policy mix combining investments in energy transition with user-pay hybrid pricing measures can facilitate cost-effective mitigation and enhance public acceptance. The proposed hybrid pricing includes cost-based electricity pricing and a two-step carbon pricing strategy that encourages early action (before 2030) for larger emitters. Finally, we demonstrate that accelerating the transition is crucial, as it reduces the economic costs of meeting emission targets by inducing further investments in energy efficiency improvement and lowering the carbon pricing levels required to close the abatement gap.